Rippling of graphitic surfaces: a comparison between few-layer graphene and HOPG. Issue 19 (2nd May 2018) - Haghighian, N.; Convertino, D.; Miseikis, V.; Bisio, F.; Morgante, A.; Coletti, C.; Canepa, M.; Cavalleri, O.
Abstract : The surface structure of Few-Layer Graphene (FLG) epitaxially grown on the C-face of SiC has been investigated by TM-AFM in ambient air and upon interaction with dilute aqueous solutions of bio-organic molecules (l -methionine and dimethyl sulfoxide, DMSO). Abstract : The surface structure of Few-Layer Graphene (FLG) epitaxially grown on the C-face of SiC has been investigated by TM-AFM in ambient air and upon interaction with dilute aqueous solutions of bio-organic molecules (l -methionine and dimethyl sulfoxide, DMSO). Before interaction with molecular solutions, we observe nicely ordered, three-fold oriented rippled domains, with a 4.7 ± 0.2 nm periodicity (small periodicity, SP) and a peak-to-valley distance in the range 0.1–0.2 nm. Upon mild interaction with the molecular solution, the ripple periodicity "relaxes" to 6.2 ± 0.2 nm (large periodicity, LP), while the peak-to-valley height increases to 0.2–0.3 nm. When additional energy is transferred to the system through sonication in solution, graphene planes are peeled off, as shown by quantitative analysis of Raman spectroscopy and X-ray photoelectron spectroscopy which indicate a neat reduction of thickness. Upon exfoliation rippled domains are no longer observed. In comparative experiments on cleaved HOPG, we could not observe ripples on pristine samples in ambient air, while LP ripples develop upon interaction with the molecular solutions. Recent literature on similar systems is not univocal regarding the interpretation of rippling. The ensemble of our comparative observations on FLG and HOPG can be hardly rationalized solely on the basis of the surface assembly of molecules, either organic molecules coming from the solution or adventitious species. We propose to consider rippling as the manifestation of the free-energy minimization of quasi-2D layers, eventually affected by factors such as interplanar stacking, and interactions with molecules and/or with the AFM tip.